Drag reduction in spatially developing turbulent boundary layers by spatially intermittent blowing at constant mass-flux - Kametani, Yukinori; Fukagata, Koji; Orlu, Ramis; Schlatter, Philipp (Journal of Turbulence, 2016)
A series of large-eddy simulations of spatially developing turbulent boundary layers with uniform blowing at moderate Reynolds numbers (based on free-stream velocity, U∞, and momentum thickness, θ) up to Reθ ≈ 2500 were performed with the special focus on the effect of intermittent (separated in streamwise direction) blowing sections. The number of blowing sections, N, investigated is set to be 3, 6, 20, 30 and compared to N = 1, which constitutes the reference case, while the total wall-mass flux is constrained to be the same for all considered cases, corresponding to a blowing amplitude of 0.1% of U∞ for the reference case. Results indicate that the reference case provides a net-energy saving rate of around 18%, which initially decreases at most 2% points for N = 3 but recovers with increasing N, where the initial reduction of the drag reduction is found to be related to the shorter streamwise length of the intermittent blowing sections. The physical decomposition of the skin friction drag through the Fukagata-Iwamoto-Kasagi (FIK) identity shows that the distribution of all components over each blowing section has similar trends, resulting in similar averaged values over the whole control region.
CRIS-Team Scopus Importer:2023-03-21
Keywords: blowing; flow control; Turbulent boundary layer